Penerapan Media Berbasis KIT IPA Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Panas Dan Perpindahannya Kelas V SDI Tanakaraeng Kecamatan Manuju Kabupaten Gowa - Nur Fitri Ramadhani; Khaeruddin Khaeruddin; Hilmi Hambali (Journal on Education, 2023)
The type of this research is Classroom Action Research. The purpose of this research is to find out whether the application of the Science Kit media can improve the science learning outcomes of class V on heat and transfer which consists of two cycles where each cycle is held in two meetings. Research procedures include planning, implementing actions, observation, and reflection. The subjects of this research were class V (five) of SDI Tanakaraeng, Gowa Regency, which consisted of 32 students. Data collection techniques in this study are by means of observation, written tests.The results showed that applying KIT IPA media could improve the learning outcomes of fifth grade students in science subjects at SDI Tanakaraeng, Gowa Regency. This can be seen from the increase in each cycle. In the initial ability (pretest) learning outcomes were obtained with an average score of 54 and a completeness percentage of 22% for that the researcher conducted cycle I and the results obtained after cycle I were an average value of 57 and a completeness percentage of 31% then the researcher conducted cycle II and experienced an increase with an average value of 80 and learning completeness of 87.5%. Based on the results of the research above, it can be concluded that the interest and results of learning science for Class V students at SDI Tanakaraeng, Manuju District, Gowa Regency through the application of the Science Kit media have increased.